Qualitative risk assessment of transmission pathways of highly pathogenic avian influenza (HPAI) virus at live poultry markets in Dhaka city, Bangladesh - SK Shaheenur Islam (2020)
© 2020 Blackwell Verlag GmbH Analysis of environmental samples obtained from the Live Poultry Markets (LPMs) of Dhaka City, Bangladesh, has revealed that the highest degree of prevalence of highly pathogenic avian influenza A (HPAI, H5N1), besides other subtypes of the LPAI virus, poses the plausible risk of transmission of these viruses between human and poultry species. The present study was conducted using the OIE risk analysis framework to assess the risk level of each pathway successively. The estimated risk parameters were integrated towards to obtain the overall risk level for each specific HPAI transmission pathway using the matrix adapted by Cristobel Zepeda accompanying other expert consultations. The relevant data obtained from published and unpublished sources, together with survey data of field observations, were used to formulate and confirm the risk pathways and their associated risks. The results revealed that the risk of the release of the HPAI virus was medium when exposure was high. Additionally, the consequence would be considered very high with a medium degree of uncertainty for all parameters. Ultimately, the overall risk for transmission was estimated as medium with a medium degree of uncertainty. The findings of this study reveal that there is a significant threat that HPAI virus transmission could occur among poultry and humans and effectively sustain within the environment of the LPMs. Our findings are primarily focused on public health considerations, the hygienic slaughter of poultry and the relevant cleaning and sanitation practices conducted in the LPMs to support evidence-based decision-making processes. The findings of the study have the potential to be used to formulate effective risk reduction measures and can be further adapted in low-resource settings without major infrastructural changes required of the LPMs. All of which would reduce the risk of HPAI virus release and further lessen the degree of exposure and transmission in established LPMs.